Big Data in Construction Perspective: Exploration of Google Cloud based Technologies and Offerings (London Journal of Engineering Research, 2023)
This paper critically explores and reviews the literature to identify the data trends and how the construction industry can benefit from big data. The big data has brought the revolutionary changes in all the industries and construction industry is also not remaining untouched. Big data engineering (BDE) and statistics are among the most crucial steps for integrating big data technology in construction. We have reviewed related papers published in the various research and education institute across the world. The current application of Big Data in construction industry is already wide spread and future opportunities like big data research into construction safety, site management, heritage conservation, and project waste minimization and quality improvements are giving it totally new dimensions.Construction industry generates large amount of data every day but this data which has huge potential but not gets utilized effectively mainly due to lack of technology adoption. This paper will try to give different perspective of Big Data with the appropriate use of Big Data Engineering, Tools and Technologies. We will also discuss the currently available tools such as computer-aided drawing (CAD) and building information modeling (BIM) and how they are providing tremendous opportunities to researcher in construction industry. We will also discuss how the rise of interest in big data is making it more effective due to the adoption of technology such as robotics, smartphones, computers and other gadgets. These gadgets helps in model development gathering data which gets used in the development of varioustechnique for Algorithm development, machine learning (ML), statistical analysis, and computational.
Keywords: two-lobe textured journal bearing; load carrying capacity; dynamic stability; critical mass of journal; threshold speed; whirl frequency ratio; cybersecurity; cyber-threats; cyber-physical compromise; critical infrastructure; smart grid; .fuel loss; congestion; intersection; journey time; long queues.